Students' Problems in the Instruction of English Literature in the EFL Context (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
This study reveals student-related problems as an existing phenomenon in the learning of English literature at the English Department. This refers to both the difficulties faced by the students and the students as a part of the problems. Using the qualitative descriptive method, the data were collected using questionnaires, observation, documentation, and Forum Group Discussion. Having been collected, the data were analyzed using qualitative data analysis offered by Miles, Huberman, and Saldana (2020) consisting of reduction, display, and conclusion phases. The findings show that there are external and internal problems. The external problems include students’ external factors, such as the difficulty of teaching materials and the ineffective teaching strategy, whereas the internal problems cover students’ affective factors, such as low reading motivation and inadequate language competence. Due to its limitation, it is suggested that further research be carried out with other subjects in another university context to verify the findings.